The Effect of Social Media-Based Digital Marketing Toward Increasing Income of MSMEs Gondanglegi Malang in Islamic Economic Perspective - ririn noviyanti; Fathin Nur Azizah (Institut Agama Islam (IAI) Al-Qolam, 2023)
Advances in technology support the sophistication of information and communication technology. This has an impact on the economic sector. That way, the economic system must innovate so that it can be in line with and in line with today's life. One of the innovations that can be done is to use a digital marketing strategy. Digital marketing is the use of digitization which is used as a forum for promotion related to products and services owned by business actors to customers through an approach strategy with an online system. According to previous research, the most active internet users in Indonesia are on social media with around 60.4%. That way marketing through social media is expected to fully contribute to economic progress. The purpose of this study was to determine digital marketing from an Islamic economic perspective and to analyze the effect of social media- based digital marketing on increasing MSME income in Gondanglegi District, Malang Regency. This type of research uses descriptive quantitative. This data collection technique used a questionnaire which was distributed to 30 MSME actors in Gondanglegi District who carried out marketing methods using social media. The results of the study show that digital marketing strategies are permissible from an Islamic perspective. In addition, statistical analysis shows that there is a significant influence between social media-based digital marketing on increasing MSME income in Gondanglegi District, Malang Regency